Analisis Struktur dan Fungsi Cerita Rakyat Karimongkong Kabupaten Sumbawa - Sukarismanti, Sukarismanti; Nurjannah, Rizky; Najamudin, Najamudin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The research focuses on exploring the structure and function of the Karimongkong folk tale through a qualitative approach. Three analytical perspectives—structural, functional, and interpretive—are employed. The data is obtained by downloading the story, and thoroughly analyzing its components such as characters, setting, theme, plot, and underlying message. The story's significance is examined within the social and cultural contexts. The findings reveal that Karimongkong portrays the journey of a determined young man from a humble background who confronts obstacles and rejection, conveying moral values of resilience, familial love, and loyalty. Set in the village of Muer within the Plampang district, the tale revolves around the themes of determination and courage in the face of challenges, progressing from character introduction to Karimongkong and his family's blissful life. While the function of this folklore is used to protect people's expectations, legalize the rules of customary institutions, regulate behavior, and create cultural identity. This research enhances comprehension of the structure and purpose of folk tales, which inspire bravery, determination, and affection.